Effects of chlorocholine chloride on pubertal development and reproductive functions in male rats. (1st February 2020) - Hou, Xiaohong; Hu, Hong; Xiagedeer, Bayindala; Wang, Pengmin; Kang, Chenping; Zhang, Qi; Meng, Qinghe; Hao, Weidong
Highlights: Chlorocholine chloride delays puberty onset in male rats. Chlorocholine chloride impairs reproductive functions of male rats. Chlorocholine chloride disturbs hypothalamic-pituitary-testicular axis. Chlorocholine chloride inhibits the secretion of kisspeptin. Abstract: Chlorocholine chloride (CCC), a plant growth retardant, may act as an endocrine disruptor. Our previous study showed that pubertal CCC exposure in rats might decrease testosterone (T) synthesis. This study observed the changes in pubertal development and reproduction of male rats exposed to CCC and its underlying mechanisms. Rats were exposed to CCC (0, 75, 137.5 and 200 mg/kg bw/day) from postnatal day 23 to 60. The results showed that CCC treatment delayed the onset of puberty and reduced the relative organ weight of prostate. Seminiferous tubules with deciduous spermatogenic cells were observed in the 200 mg/kg bw/day group. Sexual behavior was inhibited in the 137.5 and 200 mg/kg bw/day groups. Sperm motility, litter size and normalized anogenital distance (AGD) of male pups were decreased in the 137.5 and 200 mg/kg bw/day groups. Serum kisspeptin level and serum and testicular levels of T were reduced in all CCC treated groups. Crucial hormones in hypothalamic-pituitary-testicular (HPT) axis were reduced subsequently after CCC treatment. Collectively, our results demonstrated that CCC might disturb HPT axis through suppressing the secretion of kisspeptin and subsequently lead to delayed puberty onset and impaired reproductive functions.